Legal Analysis of the Monta District Expansion Plan in Bima Regency: A Regional Government Law Perspective - Syamsudin Syamsudin; Aman Ma’arij; andriadin andriadin; Erham Erham; Gufran Gufran (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
Subdistrict expansion serves as a strategic effort to enhance public service effectiveness and accelerate regional development, particularly in geographically extensive areas such as Monta Subdistrict, Bima Regency. This study aims to examine the legality of the proposed Monta District expansion within the framework of local government law and to identify key implementation challenges and strategic solutions. A normative legal research method is employed, using conceptual, statutory, and case-based approaches. The findings indicate that, administratively, the legal requirements for expansion have been fulfilled in accordance with Government Regulation No. 17 of 2018 and Article 221 of Law No. 23 of 2014. However, several deficiencies remain, including the lack of essential supporting documents such as academic manuscripts, technical assessments, approval from the Bima Regency DPRD, inclusive public participation, and institutional regulatory harmonization. This study recommends cross-sectoral coordination to expedite the expansion process and develop a comprehensive local legal framework. The findings contribute to the strengthening of regional governance in the context of decentralization and regional autonomy.